The 2010 International Power Electronics Conference - ECCE ASIA - 2010
DOI: 10.1109/ipec.2010.5543223
|View full text |Cite
|
Sign up to set email alerts
|

Common-mode voltage reduction modulation techniques for three-phase grid connected converters

Abstract: This paper experimentally investigates the performance of three-phase voltage source PWM converter, with the grid interfaced photovoltaic energy conversion system being the main application. In such applications the ground leakage current (common mode current, CMC) should be much less than an ampere and this is difficult to obtain in transformerless (direct) connected systems. With the target being reduction of the common mode voltage (CMV) and CMC, the converter performance is investigated thoroughly. Convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…This proves to a certain degree -although based on advanced assumptions-that the equivalent noise source representing the converter behaviour is a-priori the signal on the switching devices sides chopped at the switching frequency F sw . This joins some endorsed previous models such as in [19,9].…”
Section: Mathematical Developmentsupporting
confidence: 87%
See 1 more Smart Citation
“…This proves to a certain degree -although based on advanced assumptions-that the equivalent noise source representing the converter behaviour is a-priori the signal on the switching devices sides chopped at the switching frequency F sw . This joins some endorsed previous models such as in [19,9].…”
Section: Mathematical Developmentsupporting
confidence: 87%
“…Hence, during designing and for an optimal manufacturing cost and size point of view, it is important to account for the ElectroMagnetic Compatibility (EMC) constraints. In addition, within modern multisource grids -as in photovoltaic systems -common mode (CM) current, mainly flowing inside shielding structures, may cause serious safety risks, dysfunctions, and saturation effects inside magnetic circuit of EMI filters [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the simulation models as those shown in Fig. 10 are simple and sufficient for the study of basic leakage current, as demonstrated in [30].…”
Section: Leakage Current Characteristics Of the Tpvismentioning
confidence: 96%
“…The DPWM is successfully used in conventional two-level inverters [7][8][9][10][11][12][13][14]. If different phases are clamped to different voltage levels at different angles of the reference vector, different types of DPWM will be obtained.…”
Section: Introductionmentioning
confidence: 99%